Achievements of elementary school students on a knowledge test about types and properties of materials - Balać, Sanja; Mileusnić, Marija (Norma, 2025)
Summary: At an early age, children encounter various materials, describe them and classify them in their own and not always scientifically correct ways, which later makes school learning more difficult (or may complicate) them. With the aim of assessing the level of achievement of third and fourth grade students of primary school on the types and properties of materials, an examination of the concepts of hardness, brittleness, roughness, transparency and elasticity of materials was conducted. The research was conducted using a knowledge test on the aforementioned concepts, which was created according to the revised Bloom’s Taxonomy. 95 students from the "Ivo Lola Ribar" and "Avram Mrazović" primary schools in Sombor were tested, and the sample of teaching content for testing was selected from the Teaching and Learning Program for students of younger school age (from first to fourth grade). ). The analysis of the obtained data revealed that students do not have satisfactory knowledge about the types and properties of materials, while satisfactory knowledge in the research was defined by a summative score of 4 and 5 on the knowledge test. When solving tasks at different cognitive levels, students achieved the best achievements at the level of knowledge (third grade) and understanding (fourth grade), while from the third cognitive level (application) both grades achieved weaker achievements, without a clearly visible regularity in the decrease or increase in the number of points earned. Contrary to expectations, younger students achieved better results compared to older students, with the observed difference not being statistically significant. Keywords: material properties, student achievement, knowledge test, class teaching, Bloom’s taxonomy